مستوى الضغوط النفسية وعلاقتها بالانضباط المدرسي لدى معلمي المرحلة الثانوية في المدارس الحكوميّة في محافظة رام الله والبيرة - ناصر, محمد; أبوصفية, رمضان (جامعة الوادي - University of Eloued, 2022)
هدفت هذه الدراسة إلى التعرف على مستوى الضغوط النفسيّة وعلاقتها بالانضباط المدرسي لدى معلمي المرحلة الثانوية في المدارس الحكومية في محافظة رام الله والبيرة. تكّون مجتمع الدراسة من المعلمين والمعلمات العاملين في محافظة رام الله والبيرة، والبالغ عددهم الإجمالي (2576) معلماً ومعلمة، منهم (831) ذكراً و(1745) أنثى؛ أما عينة الدراسة فتكّونت من (204) معلماً ومعلمة اختيرت بالطريقة العشوائيّة البسيطة. وقد اعتمدت هذه الدراسة على المنهج الوصفي التحليلي، ومراجعة الأدبيات ذات العلاقة بموضوع البحث. توصلت نتائج الدراسة إلى أن مستوى الضغوط النفسيّة والانضباط المدرسي لدى معلمي المرحلة الثانوية في المدارس الحكومية في محافظة رام الله والبيرة جاءت بمتوسطات حسابية (3.68)، و(3.43) على التوالي وبدرجات مرتفعة. كما أظهرت نتائج هذه الدراسة في مجال الضغوط النفسية عدم وجود فروق دالة إحصائياً في متوسطات استجابات أفراد عينة الدراسة عند مستوى الدلالة (α ≤ 0.05) تعزى لمتغيرات الجنس والتخصص والمؤهل العلمي، وتوجد فروق ذات دلالة عند مستوى الدلالة (α ≤ 0.05) تعزى لمتغيرات العمر وسنوات الخبرة. كما وأظهرت نتائج هذه الدراسة في مجال الانضباط المدرسي عدم وجود فروق دالة إحصائياً في متوسطات استجابات أفراد عينة الدراسة عند مستوى الدلالة (α ≤ 0.05) تعزى لمتغيرات التخصص، والعمر، وسنوات الخبرة، وتوجد فروق ذات دلالة عند مستوى الدلالة (α ≤ 0.05) تعزى لمتغيرات الجنس، والمؤهل العلمي. بالإضافة إلى ذلك فقد أظهرت هذه النتائج إلى وجود علاقة ارتباط طردية ودالة إحصائياً بين الضغوط النفسية والانضباط المدرسي لدى معلمي المرحلة الثانوية في المدارس الحكومية في محافظة رام الله والبيرة. Abstract: This study aimed to identify the level of psychological stress and its relation to school discipline among secondary school teachers in public schools in Ramallah and the Al-Birah governorate. The study population consisted of male and female teachers who work in Ramallah and the Al-Birah governorate. Their total number is 2576 teachers, of whom 831 are males and (1745) are females. The sample of the study consisted of (204) male and female teachers chosen by a simple random method, in addition to the literature review which related to the research topic. The findings concluded that the level of psychological stress and school discipline among secondary school teachers in public schools in Ramallah and Al-Birah governorates came with arithmetic averages of ( 3.68) and (3.43), , respectively, with high degrees. Findings of the study in the field of psychological stress also revealed that there were no statistically significant differences in the main responses of the study sample participants at the significance level (a ≤ 0.05) due to the variables of age and years of experience. The findings of this study in the field of school discipline also revealed that there were no statistical differences in the average response of the study sample members at the significant level (a ≤ 0.05) due to the variables of specialization, age, and years of experience, and there were significant differences at the level of significance (a ≤ 0.05) due to gender and educational qualification. Furthermore, the findings revealed a direct and statistically significant positive relationship between psychological stress and school discipline among secondary school teachers in Ramallah and Al-Birah governorate public schools.
مقال
Keywords: الضغوط النفسية، الانضباط المدرسي، المدارس الحكومية في محافظة رام الله والبيرة; psychological stress, school discipline, Ramallah and Al-Birah governorate public schools